1999
DOI: 10.1080/026404199365948
|View full text |Cite
|
Sign up to set email alerts
|

Social support dimensions and components of performance in tennis

Abstract: The aim of this study was to explore the relationships between dimensions of social support and components of performance in tennis. A post-match performance measure was completed by 144 British tournament tennis players. Principal components analysis yielded eight components, labelled Execution of (Flexible) Plan, Loss of Composure, Feeling Flat, Positive Tension, Worry, Flow, EV ective Tactics and Double Faults. Before the match, 46 players had also completed the Interpersonal Support Evaluation List. Stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
0
39
0
4
Order By: Relevance
“…These main effects ranged from 10% to 24% (medium to large effect sizes, cf. Cohen, 1992) for effects on performance, compared with values of 3% to 10% in the Rees and Hardy (2004) study and 12% to 21% in the Rees et al (1999) study. These effect sizes are greater than the fairly modest effect sizes observed in two recent meta-analyses of the relationships of anxiety and self-confidence with performance (Craft, Magyar, Becker, & Feltz, 2003;Woodman & Hardy, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These main effects ranged from 10% to 24% (medium to large effect sizes, cf. Cohen, 1992) for effects on performance, compared with values of 3% to 10% in the Rees and Hardy (2004) study and 12% to 21% in the Rees et al (1999) study. These effect sizes are greater than the fairly modest effect sizes observed in two recent meta-analyses of the relationships of anxiety and self-confidence with performance (Craft, Magyar, Becker, & Feltz, 2003;Woodman & Hardy, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A few researchers have noted social support as an important resource within a performance context (e.g. Gould, Guinan, Greenleaf, Medbery, & Peterson, 1999;Holt & Hogg, 2002;, and recently some (Rees & Hardy, 2004;Rees, Ingledew, & Hardy, 1999) have used process-related performance measures. Using a high-level (regional to international standard) sample of tennis players, Rees and Hardy (2004) found evidence for main effects of social support and interactive effects of social support and stressors upon processes underlying performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of the perceived available support measures used in sport psychology research were originally developed to assess support in general social psychology. Concerns have been raised regarding the content validity of such measures in sport because they assess general everyday support issues and do not account for the support issues that might be of speci c relevance to high level sportspeople (Rees et al, 1999). Rees and Hardy (2000) found that, in addition to support with everyday issues, athletes required unique forms of support to help with sport-speci c demands, such as selection issues, tness concerns, and problems in training and competition.…”
mentioning
confidence: 99%
“…In sport, perceived available support has been associated with bene cial effects on self-con dence (Rees & Freeman, 2007), processes underpinning performance (Rees, Ingledew, & Hardy, 1999), performance outcome (Freeman & Rees, 2009), and vulnerability to injury (Smith, Smoll, & Ptacek, 1990). A number of the perceived available support measures used in sport psychology research were originally developed to assess support in general social psychology.…”
mentioning
confidence: 99%